Analysis of determinants of early-stage entrepreneurial activity in Russia - Elena Pawęta; Yuri Kirillov (Comparative Economic Research. Central and Eastern Europe, 2016)
Entrepreneurial activity is very important for the economic development of any country. The question often asked by researchers is: what causes growth in the level of entrepreneurial activity? In this paper we focused on the individual-level determinants of entrepreneurial activity - the attitudes and perceptions of entrepreneurship by individuals in the society. The objective of this research is to define how individual-level variables concerning opinions and beliefs in the society influence the early-stage entrepreneurship level in Russia. The research is based on the Global Entrepreneurship Monitor data, which we employ using the method of least squares in order to find linear relationships between variables. The results show that two out of presented four hypotheses have been proven. The data presented show that the entrepreneurship activity in the country is positively related to individual-level perceptions of entrepreneurship in the society. These findings may be useful for further research on entrepreneurial intentions.
Keywords: 330; entrepreneurship; entrepreneurial intentions; entrepreneurial activity